THE IMPACT OF THE DIGITAL ECONOMY ON ECONOMIC GROWTH - Baxtiyarjon Bulturbayevich, Mullabayev; Baxriddin Jurayevich, Mahmudov (IJBLE Scientific Publications Community Inc., 2020)
The article outlines the importance of the digital economy in the economic growth of the Republic of Uzbekistan, its benefits, reforms and recommendations made by the government for its development.